Developing an innovative clinical governance assessment framework for Dental Schools in Iran - Dehghanian, D; Heydarpoor, P; Namdari, M; Khoshnevisan, MH (Journal of Contemporary Medical Sciences, 2019)
Objectives: The aim of this study was to develop and validate a DCG assessment framework for use in local dental schools in Iran. Methods: A mixed method (qualitative and quantitative) was used in the present investigation. The study was performed in 3 steps, including: a) thorough literature review, b) focused group discussion and c) Application of validated instrument. The content validity index (CVI) and content validity ratio (CVR) were calculated for each question. The Cronbach's alpha coefficient was calculated to evaluate the internal consistency and reliability for this questionnaire. The Smart PLS software was used for calculation of Goodness of Fit (GOF) for confirmatory factorial analysis to determine construct validity of this questionnaire. Results: Initially, 140 items covering 7 DCG domains were identified after comprehensive literature review. Ten specialists participated in the expert panel, rating independently on the necessity, relevancy, simplicity and clarity of each question. Expert’s ratings were used to calculate the validity for each question. The questions with CVI lower than 0.79 and the CVR less than 0.62 were excluded. Reliability analysis was conducted by calculating intra class coefficient (ICC) and Cronbach's alpha coefficient which were 0.88 and 0.92 respectively. This shows good reliability and internal consistency of the questionnaire. Construct validity determined by computing Goodness of Fit index. The result was 0.622, which indicates a good level of construct validity. After validation process, 124 out of 140 questions left to cover the 7 domains of DCG in our newly developed and validated framework. Conclusions: The newly developed and standardized DCG framework can be used for assessment of compliance level among Iranian dental schools at the national level.